Menguak Hambatan Graduasi: Dinamika Program Keluarga Harapan (PKH) pada Keluarga Penerima Manfaat (PKM) - Hartadi, Muhammad Irfan; Arif, Arif; Poerwanti, Sari Dewi (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
The Program Keluarga Harapan (PKH) is expected to enhance human resources quality, transform the behavior of participants of the Recipient Family Welfare (KPM) PKH who do not support efforts to improve welfare, and break the intergenerational poverty cycle. Graduation, as the fourth phase of PKH, refers to the process of ending membership status of KPM families in the program. However, there are barriers hindering graduation achievement. This study aims to analyze, examine, and describe the deceleration of PKH graduation among KPM in Glundengan Village, Wuluhan District, Jember Regency. The research employs a qualitative descriptive approach. Data collection utilizes non-participant observation, semi-structured interviews, and documentation. The data analysis method involves data collection, data reduction, data display, and conclusion drawing. Triangulation of techniques and sources is used to validate the data. The research findings identify inhibiting factors for achieving self- graduation goals in Glundengan Village, including family human resource factors related to misuse of aid allocation, mindset, ethnic diversity, as well as other factors such as the amount of aid received and the PKH mentoring mechanism.